How to motivate with speech. Findings from acoustic phonetics and pragmatics - Voße, Jana; Niebuhr, Oliver; Wagner, Petra (Frontiers in Communication, 2022)
In the present work, we describe and discuss two studies in the field of motivating-speech research. The studies investigate voice-quality features (study 1) and pragmatic aspects (study 2) in German motivating speech, thereby adding to the current state-of-the-art in understanding motivating speech and language1. We find indications that a low amount of breathiness, a more periodic signal and a balanced distribution of specific pragmatic elements contribute to a motivating impact in German.